Treatment of Poisoning Cases from Certain Narcotic Substances Using a Nanocomposite - Hussein, Tayis Fattah Abdulrahman; Alwan, Liqaa Hussein (American Journal of Bioscience and Clinical Integrity, 2025)
This work focuses on the development of new type of activated carbon produced from waste branches of Melia azedarach collected in Samarra city. Characterization studies demonstrated that the prepared carbon is in nanometer size. The microparticle sizes were confirmed to be smaller than 100 nm by X-ray diffraction and specific sizes of 7.48 nm, 6.06 nm, and 2.71 nm were obtained. The free vibration peak in FT-IR did not appear, which showed that the activated carbon was chemically inactive. The SEM images for the particles at 10 µm and 200 nm scale indicated that the particles consisted of abundant pore structure like transparent, thin, folded, and fluffy sheet. Energy-dispersive X-ray spectroscopy indicated the high carbon content of the synthesized material. The fabricated carbon was used in the adsorption of Chlorpheniramine from aqueous solutions. Adsorption mechanism was investigated using Freundich and Temkin isotherm, and the result showed that the Freundlich model, whose correlation coefficient (R² = 0.9993) was closer to unity than the Temkin model (R² = 0.982). The thermodynamics study revealed that the process of adsorption is spontaneous (∆Gº < 0), with falling in randomness (∆Sº < 0) and that it is exothermic (∆Hº = -60,535.9 J/mol). Moreover, the kinetic study revealed that the adsorption was of pseudo-first-order type.